Characterization of green building materials manufactured from canola oil and natural zeolite - Balo, Figen (Springer, 2015)
The main objective of this paper was to evaluate the feasibility and performance of building materials similar to gas concrete using epoxidized canola oil (ECO), fly ash (FA), natural clay (C) and natural zeolite (Z). In this study, ECO, C, FA [wastes produced in AfAYin-Elbistan (KahramanmaraAY, Turkey) thermal power station] and Z are used for producing building material. FA, C and Z were used as raw materials for producing the samples. ECO was used for binding. Density, thermal conductivity and compressive-tensile strength were decreased with the increase of ECO, FA and Z at all levels of replacements. Moreover, increasing process temperatures decreased density, thermal conductivity and compressive-tensile strength. Abrasion loss and water absorption were increased with the increase of ECO, FA, Z ratios and process temperatures.
Keywords: Building material; Canola oil; Clay; Fly ash; Zeolite